Solid-liquid equilibria of Sorel phases and Mg (OH)2 in the system Na-Mg-Cl-OH-H2O. Part I: experimental determination of OH− and H+ equilibrium concentrations and solubility constants at 25°C, 40°C, and 60°C - Pannach, Melanie; Paschke, Iris; Metz, Volker; Altmaier, Marcus; Voigt, Wolfgang; Freyer, Daniela (Frontiers in Nuclear Engineering, 2023)
Solid phase formation was studied by suspending MgO and Mg(OH)2 in NaCl saturated MgCl2-solutions at 25°C. Mg(OH)2 and the 3-1-8 Sorel phase were identified as the stable solid phases, while the 5-1-8 Sorel phase is metastable. Equilibration at 40°C did not lead to any solid phase changes. Both OH- and H+ equilibrium concentrations were analyzed as a function of MgCl2 concentration at 25 °C and 40 °C. In addition to the already published solid-liquid equilibria for the ternary system Mg-Cl-OH-H2O (25 to 120°C) in Pannach et al. 2017, the equilibrium H+ concentrations (pHm) determined at 25 °C, 40 °C and 60 °C are now reported. Analyzing these data together with known ion-interaction Pitzer coefficients, the solubility constants for Mg(OH)2 and the 3-1-8 phase at these three temperatures, for the metastable 5-1-8 phase at 25 °C and for the 2-1-4 phase at 60 °C have been consistently calculated.